2001
DOI: 10.1093/emboj/20.23.6772
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin and calnexin in the endoplasmic reticulum are important for phagocytosis

Abstract: Calreticulin and calnexin are Ca 2+-binding proteins with chaperone activity in the endoplasmic reticulum. These proteins have been eliminated by gene replacement in Dictyostelium, the only microorganism known to harbor both proteins; family members in Dictyostelium are located at the base of phylogenetic trees. A dramatic decline in the rate of phagocytosis was observed in double mutants lacking calreticulin and calnexin, whereas only mild changes occurred in single mutants. Dictyostelium cells are profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(153 citation statements)
references
References 56 publications
7
143
1
Order By: Relevance
“…3) Mutants deficient in the ER proteins calreticulin and calnexin are deficient in phagocytosis. Moreover, green-fluorescent protein-labeled calreticulin and calnexin demonstrated a link between the ER and phagocytic cup (50). Thus, we suggest that a strand of the ER mediates the line of communication indicated by the present study.…”
Section: Discussionsupporting
confidence: 69%
“…3) Mutants deficient in the ER proteins calreticulin and calnexin are deficient in phagocytosis. Moreover, green-fluorescent protein-labeled calreticulin and calnexin demonstrated a link between the ER and phagocytic cup (50). Thus, we suggest that a strand of the ER mediates the line of communication indicated by the present study.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have suggested that the ER participates in phagocytosis. Recruitment of ER to the site of phagocytosis has been suggested by studies showing the presence of ER-associated proteins on purified phagosomes (12) and the accumulation of GFP-labeled calreticulin and calnexin, two proteins of the ER, at the phagocytic cup (26). In addition, electron microscopy studies indicate that phagosomes maintain a thin filament of ER connecting them with the plasma membrane (27).…”
Section: Discussionmentioning
confidence: 98%
“…For example, in Dictyostelium cells, calreticulin and calnexin are important for yeast particle phagocytosis. 20 Moreover, calreticulin has been identified as a marker for engulfment of apoptotic cells by Drosophila phagocytes. 21 Since calreticulin is detected on the surface of apoptotic cells as well as on phagocytes, 22 several modes of action for calreticulin have been proposed to explain its role in engulfment.…”
Section: Positive Regulators Of Uptake Dying Cellmentioning
confidence: 99%